2017
DOI: 10.1093/ecco-jcc/jjx002.074
|View full text |Cite
|
Sign up to set email alerts
|

DOP037 A model for prediction of early surgery and complications in paediatric Crohn's disease: results of the prospective GROWTH CD study

Abstract: Abstracts of the 12 th Congress of ECCO -European Crohn's and Colitis Organisation S49of cells homozygous for high affinity FcgRIIIa158V compared to low affinity FcγRIIIa158F.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Based on previous data, biomarkers in the stool are considered to be the most sensitive laboratory parameters when assessing the endoscopic and histological activity of inflammation (1,6). It has been shown that the concentration of the neutrophil-derived marker, faecal calprotectin (FC), is associated with endoscopic activity scales and reflects mucosal healing (1,(15)(16)(17)(18)(19). Moreover, a correlation was demonstrated in the comparison of FC levels and transmural or deep remission (13).…”
Section: What Is Newmentioning
confidence: 99%
“…Based on previous data, biomarkers in the stool are considered to be the most sensitive laboratory parameters when assessing the endoscopic and histological activity of inflammation (1,6). It has been shown that the concentration of the neutrophil-derived marker, faecal calprotectin (FC), is associated with endoscopic activity scales and reflects mucosal healing (1,(15)(16)(17)(18)(19). Moreover, a correlation was demonstrated in the comparison of FC levels and transmural or deep remission (13).…”
Section: What Is Newmentioning
confidence: 99%